The Effect of Work Motivation and School Climate on the Professionalism of Mathematics Teachers in SMAN Kota Pekanbaru - Marnita, Eva; Isjoni; Chairilsyah, Daviq (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Teacher professionalism is one of the variables that determines the success of education in the future. Based on the observation results, it is known that teacher professionalism is still low. This study seeks the effect of work motivation and school climate on teacher professionalism. This research was conducted in Pekanbaru Riau in 2024. The research sample was 130 Mathematics teachers. The sampling technique used simple random sampling with data collection techniques using questionnaires. The data analysis techniques used were simple linear regression and multiple linear regression. The research results reveal that 1) there is an effect of work motivation on the professionalism of mathematics teachers at SMAN Pekanbaru, 2) there is an effect of school climate on the professionalism of mathematics teachers at SMAN Pekanbaru, and 3) there is an effect of work motivation and work climate on the professionalism of mathematics teachers at SMAN Pekanbaru. Based on the research results, the regression equation Y = 7.954 + 0.157 obtained the meaning that each unit increasing in work motivation and school climate scores together can increase teacher professionalism scores by 0.157 and 0.661 respectively at a constant of 7.954. Therefore, it can be said that the higher the work motivation and the better the school climate as well as the greater the professionalism of Mathematic teachers at Pekanbaru State High School.